"The State Pulled a Fast One on Us": A Critical Policy Analysis of State-Level Policies Affecting English Learners From District-Level Perspectives. Issue 1 (January 2019) - Sampson, Carrie
States' increasing involvement in educational policy making can play a significant role in how school districts provide equitable educational opportunities. Guided by critical policy analysis, the purpose of this article is to examine state-level policy pertaining to English learners (ELs) from district-level perspectives. Based on interview and archival data from a multiple case study of three metropolitan school districts in different states, district-level perspectives illustrate how these state-level policies were symbolic, restrictive, or exclusionary toward ELs. The results also demonstrate ways that districts advocated, engaged, resisted, and navigated state-level policies and politics. Based on these findings, I argue that state-level policies and related politics can compromise school districts' ability to provide ELs with adequate educational opportunities.